A tri-layer thin film containing graphene oxide to protect zinc substrates from wear. (1st June 2018) - Wang, Ying; Gu, Zhengpeng; Yuan, Ningyi; Chu, Fuqiang; Cheng, Guanggui; Ding, Jianning
Abstract: Due to its excellent properties, Zn alloy is widely used in daily life. However, the poor wear-resisting properties of Zn alloys limits their application. In this paper, a tri-layer thin film consisting of 3-aminopropyltriethoxysilane (APS), graphene oxide (GO) and perfluoropolyethers (PFPE) were successfully prepared on the surface of Zn alloy to improve the wear-resisting properties. The as-prepared tri-layer thin films were characterized by atomic force microscopy, Raman spectroscopy, x-ray photoelectron spectroscopy and contact angle measurement. In addition, the tribological properties of the as-prepared tri-layer thin films were studied on a ball-on-plate tribometer and the morphologies of worn surfaces were observed using 3D noncontact interferometric microscope. Compared with the control samples, the tri-layer thin films showed excellent friction-reducing and wear-resisting properties, which was attributed to the synergistic effect of the GO as the load-carrying layer and the PFPE as the lubricating layer.